Comparative Analysis of YOLOv8 and YOLOv11 for Wildlife Detection in Natural Habitats - FELIX CORPUTTY; AHMAD SULTHON JAUHARI; DARIELE ZEBADA SANUWU GEA; IVAN FEBRIANTO LALO; RIFKI RAHMAN NUR IKHSAN; ADE ADITYA RAMADHA (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2026)
Wildlife monitoring in natural habitats remains difficult due to occlusion, camouflage, and varying illumination, which limit the performance of conventional object detection systems. Although recent YOLO-based models have shown strong potential, systematic comparisons between newer architectures in real ecological environments are still limited. This study evaluates YOLOv8 and YOLOv11 using 6,165 images from 14 wildlife classes collected at Taman Buru Gunung Masigit Kareumbi, with data augmentation applied to improve robustness. Performance is evaluated using a quantitative comparative approach based on precision, recall, mAP 0.5, and mAP 0.5:0.95. The results indicate that YOLOv11 achieves higher detection accuracy with an mAP 0.5:0.95 of 0.894.